2010
DOI: 10.1161/hypertensionaha.109.134205
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and the Osteogenic Regulation of Vascular Calcification

Abstract: A rterial biomineralization processes have been afflicting humans for Ն5 millennia, as realized in 2003 via the computed tomographic imaging of Ö tzi, the intriguing "ice mummy" discovered in the Tyrolean Alps. 1 Patchy abdominal atherosclerotic calcification was readily detected in the postmortem of this Ϸ40-year-old hunter of the early Copper Age, by 2000 years a predecessor of King Tutankhamen. 1 Today, an epidemic of vascular calcification is emerging within our aging and dysmetabolic populace. 2,3 Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
159
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(171 citation statements)
references
References 188 publications
(236 reference statements)
3
159
0
9
Order By: Relevance
“…S3C). Several studies, including ours, have shown that macrophages promote arterial calcification (27)(28)(29), and other evidence indirectly suggests that Notch signaling also regulates calcification (30). Ab treatment significantly decreased advanced calcification (von Kossa) and osteogenic activity (alkaline phosphatase activity, ALP) in atherosclerotic lesions (Fig.…”
Section: Characterization Of Dll4 Expression and The Effects Of Neutrmentioning
confidence: 59%
“…S3C). Several studies, including ours, have shown that macrophages promote arterial calcification (27)(28)(29), and other evidence indirectly suggests that Notch signaling also regulates calcification (30). Ab treatment significantly decreased advanced calcification (von Kossa) and osteogenic activity (alkaline phosphatase activity, ALP) in atherosclerotic lesions (Fig.…”
Section: Characterization Of Dll4 Expression and The Effects Of Neutrmentioning
confidence: 59%
“…Several experimental and clinical studies have reported that inflammatory biomarkers such as tumor necrosis factor‐α, IL‐6, vascular adhesion molecule‐1, macrophage, and thrombomodulin were systemically or locally increased in the presence of ECF excess 39, 40. ECF excess directly induces a phenotype change in VSCMs and indirectly induces oxidative stress, which increases the production of bone morphogenetic protein 2 and endothelial cell–derived microparticles in endothelial cells, thereby enhancing the osteogenic signal acting on VSMCs 41, 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…ALP hydrolyzes pyrophosphate, a potent calcification inhibitor, thereby favoring calcium salts deposition at tissue level. 36,37 Inhibition of ALP activity was able to reduce calcifications in vascular smooth muscle cells in the NPP1 (ecto-nucleotide pyrophosphatase/phosphodiesterases-1) and ANK (ankyrin)-deficient mice, 38 an experimental model characterized by extensive aortic calcification. Thus, ALP may be an active player in human atherosclerosis, a hypothesis in line with observational We graphically reported the competitive interaction between serum phosphorus (below/above the median value) and alkaline phosphatase (ALP) levels.…”
Section: Discussionmentioning
confidence: 99%